Analysis of Access Quality and Health Services on the Effectiveness of Health Insurance System - Siti Rofiatun Rosida (Miracle Journal Get Press, 2024)
In Indonesia, the National Health Insurance (JKN) program through BPJS Kesehatan has been launched with the aim of improving accessibility and quality of health services for the entire population. However, despite the existence of an extensive insurance system, challenges to the effectiveness of this system still exist, particularly in terms of access, quality of care, and health facility management (Dinkes Kulonprogo, 2018; Tahir, 2017). This study aims to analyze the relationship between access, quality of health services, and the effectiveness of the health insurance system, as well as how these factors affect the success of the health insurance program in improving public health status. This study uses a quantitative approach with a cross-sectional design, where data on access, quality, and health services are collected simultaneously from health insurance participants, especially BPJS Kesehatan users. The t table price at the 5% error rate = 1.98 and 1% error rate = 2.617. Thus the H1 hypothesis can be accepted because there is a positive relationship between X and Y as evidenced by the processing results of t count = 17.195 > t table = 1.98. This study suggests that to improve the effectiveness of JKN implementation through BPJS health, continuous improvement is needed, especially to instill government concern for the poor.